Restrictive and permissive alcohol policies during the COVID-19 pandemic and their association with alcohol consumption in the United States - Lemp, Julia M.; Kilian, Carolin; Bright, Sophie; Kerr, William C.; Llamosas-Falcón, Laura; Mulia, Nina; Rehm, Jürgen; Probst, Charlotte (International journal of drug policy, 2025)
Background - Early in the COVID-19 pandemic, alcohol researchers anticipated that psychological distress and changes in alcohol availability would impact alcohol consumption patterns. While psychological distress was expected to increase alcohol use, particularly among vulnerable groups, restrictive alcohol policies might have led to reduced consumption. This study examined the complex relationship between psychological distress, alcohol policies, alcohol consumption, and their interactions with sociodemographic factors during the COVID-19 pandemic in the US. - Methods - We used 2020-21 US Behavioral Risk Factor Surveillance System Survey (BRFSS, N = 726,962 adults) data to analyze associations between psychological distress, alcohol policy scores, and alcohol consumption, considering age, sex, education, race and ethnicity, and COVID-19 government response as covariates in a zero-inflated multi-level regression. State-level monthly alcohol policy scores derived from Alcohol Policy Information System data reflect the restrictiveness and permissiveness of alcohol policies implemented during the COVID-19 pandemic. - Results - Psychological distress and exposure to restrictive policies increased the likelihood of abstaining from alcohol in the past month, although the observed effects were small. Among past-month drinkers, distress and restrictive policies were associated with slightly higher average daily consumption in pure alcohol grams/day. Younger respondents were more likely to abstain from alcohol when exposed to restrictive policies, while permissive policies correlated with higher drinking prevalence and heavy episodic drinking occurrence among those with higher education. - Conclusion - Alcohol policies and psychological distress during the COVID-19 pandemic were linked to both lower and higher alcohol consumption in different population subgroups. Restrictive and permissive policies had diverging associations with consumption patterns across subgroups. While effect sizes were modest, they could translate into meaningful changes in alcohol consumption at the population level, especially during prolonged times of crisis.